In situ deposition of conducting polymer on metal organic frameworks for high performance hybrid supercapacitor electrode materials. (1st August 2022) - Shi, Liuwei; Yang, Wenyao; Zha, Xiaoting; Zeng, Qi; Tu, Dan; Li, Yi; Yang, Yajie; Xu, Jianhua; Chen, Fujia
Abstract: Metal organic frameworks (MOFs) attract great attention in electrochemical energy storage devices owing to high porosity, adjustable structure and abundant active sites. Nevertheless, their cycle stability and rate property are far unsatisfied to construct high performance devices due to the poor conductivity and structure ability. Herein, a high conductive and stable Ni-based metal organic framework (Ni-MOF)/poly(3, 4-ethylenedioxythiophene) (PEDOT) composite is synthesized from Ni-MOF nanosheets and 3, 4-ethylenedioxythiophene(EDOT) monomer via an in situ chemical vapor polymerization (CVP) method. The covering of conducting PEDOT on Ni-MOF results in significantly improved conductivity and electrochemical performance. The Ni-MOF/PEDOT composite exhibits an ultrahigh specific capacitance of 1401 F g −1 and the retention of specific capacitance is maintained over 80% subsequent to 1000 cycles at 10 A g −1 . Moreover, an asymmetric supercapacitor (ASC) based on Ni-MOF/PEDOT and activated carbon (AC) is assembled, which achieves an energy density of 40.6 Wh kg −1 at a power density of 450 W kg −1 . Graphical abstract: The high conductive and structure stable Ni-based metal organic frameworks (NiMOF)/poly(3, 4-ethylenedioxythiophene) (PEDOT) composite has been synthesized from Ni-MOF nanosheets and 3, 4-ethylenedioxythiophene (EDOT) monomer via an in-situ chemical vapor polymerization (CVP) method. Unlabelled Image Highlights: Ni-MOF/PEDOT composite was successfully synthesized via an in-situ CVP method. Ni-MOF/PEDOT composite exhibits an ultrahigh specific capacitance about 1401 F g −1 . PEDOT significantly improves the cycle life of the composite electrode and reduces interface resistance.